MORC2 is a phosphorylation-dependent DNA compaction machine - Winnie Tan; Jeongveen Park; Hariprasad Venugopal; Jieqiong Lou; Prabavi Shayana Dias; Pedro L. Baldoni; Kyoung-Wook Moon; Toby A. Dite; Christine R. Keenan; Alexandra D. Gurzau; Joonyoung Lee; Timothy M. Johanson; et al. (Nature Communications)
Abstract The Microrchidia (MORC) family of chromatin-remodelling ATPases is pivotal in forming higher-order chromatin structures that suppress transcription. The exact mechanisms of MORC-induced chromatin remodelling have been elusive. Here, we report an in vitro reconstitution of full-length MORC2, the most commonly mutated MORC member, linked to various cancers and neurological disorders. MORC2 possesses multiple DNA-binding sites that undergo structural rearrangement upon DNA binding. MORC2 locks onto the DNA using its C-terminal domain (CTD) and acts as a clamp. A conserved phosphate-interacting motif within the CTD was found to regulate ATP hydrolysis and cooperative DNA binding. Importantly, MORC2 mediates chromatin remodelling via ATP hydrolysis-dependent DNA compaction in vitro, regulated by the phosphorylation state of its CTD. These findings position MORC2 CTD phosphorylation as a critical regulator of chromatin remodelling and a promising therapeutic target.